Evidence of imbalanced adaptation between muscle and tendon in adolescent athletes. Issue 4 (27th December 2013) - Mersmann, F.; Bohm, S.; Schroll, A.; Boeth, H.; Duda, G.; Arampatzis, A.
<x xml:space="preserve">Abstract</x> Adolescence may be regarded as a critical phase of tissue plasticity in young growing athletes, as the adaptation process of muscle‐tendon unit is affected by both environmental mechanical stimuli and maturation. The present study investigated potential imbalances of knee extensor muscle strength and patellar tendon properties in adolescent compared with middle‐aged athletes featuring long‐term musculotendinous adaptations. Nineteen adolescent elite volleyball athletes [(A), 15.9 ± 0.6 years] and 18 middle‐aged competitively active former elite volleyball athletes [(MA), 46.9 ± 0.6 years] participated in magnetic resonance imaging and ultrasound‐dynamometry sessions to determine quadriceps femoris muscle strength, vastus lateralis morphology and patellar tendon mechanical and morphological properties. There was no significant age effect on the physiological cross‐sectional area of the vastus lateralis and maximum knee extension moment (P > 0.05) during voluntary isometric contractions. However, the patellar tendon cross‐sectional area was significantly smaller (A: 107.4 ± 27.5 mm2; MA: 121.7 ± 39.8 mm2) and the tendon stress during the maximal contractions was significantly higher in adolescent compared with the middle‐aged athletes (A: 50.0 ± 10.1 MPa; MA: 40.0 ± 9.5 MPa). These findings provide evidence of an imbalanced development of muscle strength and tendon mechanical and morphological properties in adolescent athletes, which may have implications for the risk of tendon overuse injuries.